Tribal women : yesterday, today, and tomorrow - Chaudhary, S. N. (Rawat Publications, 2015)
Papers presented at the two days National Seminar entitled "Tribal Women: Status, Challenges, and Possibilities" organized by Tribal Research and Development Institute, Bhopal in March 2013.